IMPORTANCE OF ASSESSING READING SKILL OF LANGUAGE LEARNERS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article presents the importance of assessment as one of the most effective steps in teaching English. Moreover, developing reading comprehension skills in teaching English is more explored by many researchers [1, 2]. Recent research highlight a few considerations exploring measuring reading comprehension that is most typically performed among university students.